Morphological features in eyes with endophthalmitis after cataract surgery – histopathology and optical coherence tomography assessment. (26th September 2015) - Solborg Bjerrum, Søren; Prause, Jan Ulrik; Fuchs, Josefine; la Cour, Morten; Kiilgaard, Jens F.
Abstract: Purpose: To assess the ocular damage that occurs in eyes with postoperative endophthalmitis after cataract surgery (PE) based on optical coherence tomography (OCT) retinal scans of PE eyes and histological specimens of eyes removed due to PE. Methods: Case–control study and case series. Fifty‐one patients who had previously developed PE were clinically examined with OCT scans of the retina of both eyes. Histological specimens of 10 removed PE eyes were studied. Results: The OCT scans showed that PE eyes had a statistically significantly higher frequency of hyperdense elements on the internal limiting membrane (ILM) of the retina (14 eyes versus 3 eyes, p = 0.015) and a higher degree of retinal atrophy temporal to the fovea (13 eyes versus 1 eye, p = 0.013) compared to fellow eyes. The histopathological analyses showed the formation of epiretinal membranes, derangement of all retinal layers with a reduced number of nuclei in the nuclear layers, loss of photoreceptor outer segments and massive retinal gliosis. Conclusions: Optical coherence tomography scans of the retina and histopathology analyses provide insights in the pathological process occurring in PE.